The Selective NMDA Receptor GluN2B Subunit Antagonist CP-101,606 with Antidepressant Properties Modulates Cytochrome P450 Expression in the Liver - Ewa Bromek; Anna Haduch; Marta Rysz; Joanna Jastrzębska; Renata Pukło; Olga Wójcikowska; Przemysław Jan Danek; Władysława Anna Daniel (MDPI AG, 2021)
Recent research indicates that selective NMDA receptor GluN2B subunit antagonists may become useful for the treatment of major depressive disorders. We aimed to examine in parallel the effect of the selective NMDA receptor GluN2B subunit antagonist CP-101,606 on the pituitary/serum hormone levels and on the regulation of cytochrome P450 in rat liver. CP-101,606 (20 mg/kg ip. for 5 days) decreased the activity of CYP1A, CYP2A, CYP2B, CYP2C11 and CYP3A, but not that of CYP2C6. The alterations in enzymatic activity were accompanied by changes in the CYP protein and mRNA levels. In parallel, a decrease in the pituitary growth hormone-releasing hormone, and in serum growth hormone and corticosterone (but not T3 and T4) concentration was observed. After a 3-week administration period of CP-101,606 less changes were found. A decrease in the CYP3A enzyme activity and protein level was still maintained, though no change in the mRNA level was found. A slight decrease in the serum concentration of corticosterone was also maintained, while GH level returned to the control value. The obtained results imply engagement of the glutamatergic system in the neuroendocrine regulation of cytochrome P450 and potential involvement of drugs acting on NMDA receptors in metabolic drug-drug interactions.